What Does This Mean for Graduate Education in Marriage and Family Therapy? Commentary on "The Divide Between 'Evidenced-Based' Approaches and Practitioners of Traditional Theories of Family Therapy" - Stith, Sandra M. (My University, 2014)
The Dattilio, Piercy, and Davis article is a welcome addition to the conversation focusing on how to bridge the divide in the MFT field between research and practice. The present commentary challenges us to see the divide as an indictment of our training programs resulting from a lack of focus on MFT research. Suggestions for increasing expectations for students to monitor client progress, get involved in research at all levels, and for doctoral students to expect to be able to conduct independent, fundable research in the MFT field when they leave their programs are offered.
Keywords: Doctoral education; Progress monitoring; Research training